Acute Abdominal Pain in Pregnancy: How to Image When Push Comes to Shove - Chen , I.; Pomykala , K.; Patel , M.; Bahrami , S.; ,; , (Seram, 2021)
Background Information: Deciding what imaging to perform on pregnant patients is challenging. Educational Goals/Teaching Points: The teaching points of this education exhibit include understanding the risks and benefits of different imaging modalities for a pregnant patient and her fetus in the setting of acute abdominal pain. We will review the risks to the fetus associated with radiation exposure and contrast agents. Additionally, we will discuss recommended algorithms for imaging studies in pregnant patients based on maternal symptoms. And lastly, we will include examples of common causes of acute abdominal pain in pregnant patients. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: The presentation outline includes covering the risks and benefits of ultrasound, MRI, radiographs and CT in pregnant patients, current guidelines on contrast administration to pregnant patients, the radiation risks to the fetus, review of guidelines for imaging studies to perform on pregnant patients based on symptoms, and finally multimodality imaging appearance of various causes of acute abdomen in the pregnant patient including appendicitis, small bowel obstruction, diverticulitis, colitis, inflammatory bowel disease, sources of GI bleeding, cholecystitis, choledocholithiasis, ovarian torsion, pelvic inflammatory disease, fibroid degeneration, placental abruption, and trauma. Conclusion: When imaging the pregnant patient, knowledge about the risks and the benefits of the imaging modality, radiology guidelines and possible imaging algorithms is essential.